Nontoxic Goiter (NTG) and Radioiodine: What Do Patients Think About It? Quality of Life in Patients with NTG Before and After 131-I Therapy - Kaniuka-Jakubowska, Sonia; Lewczuk, Anna; Majkowicz, Mikołaj; Piskunowicz, Maciej; Mizan-Gross, Krystyna; Zapaśnik, Adam; Kaszubowski, Mariusz; Lass, Piotr; Sworczak, Krzysztof (Frontiers in Endocrinology, 2018)
OBJECTIVE: Despite numerous publications regarding nontoxic goiter (NTG) treatment, and an increasing interest in patients’ quality of life, few studies present the outcome of 131-I treatment from the patients’ perspective. Our study’s main aim was to verify whether there is any improvement in life quality following131-I treatment. MATERIALS AND METHODS: 35 patients with NTG qualified to participate in the study. All patients completed a Thyroid-Related Health-Related Quality of Life (Thy-R-HRQoL) questionnaire created by us and the Medical Outcomes Study 36-item Short Form (SF-36), right before and one year after 131- I. RESULTS: We observed an improvement in 6 out of 8 SF-36, and 3 out of 7 Thy-R-HRQoL domains. In comparison with the control group, we observed worse results in 2 out of 8, prior to treatment, and 1 out of 8 of SF-36 afterwards, as well as in all Thy-R-HRQoL domains. We did not find any correlation between improvement of Thy-R-HRQoL and SF-36 and goiter size reduction, except for Bodily Pain. There was also no correlation between improvement of SF-36 and Thy-R-HRQoL domains, and goiter size before treatment. The older the patient, the less noticeable improvement was observed in Physical and Social Functioning, and Vitality in SF-36, but age had no influence on the assessment by Thy-R-HRQoL. CONCLUSIONS: Radioiodine treatment improves life quality in patients with NTG. Use of the Health-Related Quality of Life questionnaire should be taken into consideration when evaluating life quality of patients with NTG. Relentless pursuit of maximal goiter size reduction in 131-I treatment is worth consideration. In our study, life quality improvement, did not depend directly on the goiter size reduction. Life quality improvement after 131-I might not depend on initial goiter size, and for certain domains of SF-36 might be less clearly expressed in older patients.